(untitled) (Research, Society and Development, 2025)
Hospitalization is a process that involves admitting patients to healthcare units for treatments that require continuous monitoring and specialized care. In this context, the objective of this study was to assess the oral health profile of hospitalized patients by analyzing clinical and epidemiological variables. Hospitalization, especially in Intensive Care Units (ICUs), can significantly compromise oral health due to inadequate oral hygiene, dietary changes, medication use, and invasive procedures. The inclusion of dental surgeons in multidisciplinary hospital teams is recommended by the Brazilian Health Regulatory Agency (ANVISA) as a strategy to prevent healthcare-associated infections (HAIs). This observational, quantitative, and descriptive study evaluated 166 patients hospitalized through the Brazilian Unified Health System (SUS) in hospitals in the region of Lavras, between August 2024 and January 2025. Data collection included intraoral clinical examinations and variables such as gender, age, place of hospitalization, use of mechanical ventilation, type of diet, length of stay, and level of consciousness. The results showed that 67.47% of the patients were admitted to ICUs, with a mean age of 66.68 years, predominance of males, and high functional dependency. ICU patients had longer hospital stays, greater use of mechanical ventilation and non-oral diets, and more compromised levels of consciousness. Statistically significant differences were found between ICU and ward patients in terms of hospital stay, mechanical ventilation, and consciousness status. The study concludes that the clinical profile of critically ill patients requires specific and integrated care strategies, with a focus on multidisciplinary actions and the inclusion of dental care to prevent complications and promote patient recovery.